CagL amino acid sequence polymorphism of Helicobacter pylori in Vietnamese patients with gastroduodenal diseases - Tran, Ha Duy Khang; Nguyen, Thi Mai Ngan; Thai, Thi Hong Nhung; Pham, Van Linh (Tạp chí Y Dược Huế, 2026)
Background: H. pylori CagA protein plays the most critical pathogenesis role of gastroduodenal diseases. CagA translocation is dependent on the CagL protein encoded by the cagL gene. Objectives: This study aimed to investigate CagL amino acid sequence polymorphisms of H. pylori and its associations with gastroduodenal diseases. Materials and methods: The cagL partial nucleotide sequences of 72 H. pylori strains from Vietnamese patients with gastroduodenal disorders were investigated via Sanger sequencing, then were translated into amino acid sequences. Results: The findings showed nine variants of amino acid polymorphism within the CagL hypervariable motif at residues 58–62, in which the DEIGK variant was the most prevalent, accounting for 40.28%, the DKIGK variants represented 30.56%, both DKMGE and DTTGE variants accounted for 8.33%. The five remaining variants, including YEIGK, NEIGQ, NKIGQ, DEIGQ and DTIGK, had low frequencies (1.39–4.17%). Notably, we observed a novel amino acid sequence polymorphism pattern at residues 140-144 with four variants as EAELQ, EGKLK, LGKLK, and EAKLQ, which accounted for 61.11%, 30.56%, 5.56%, and 2.78%, respectively. Stratifying gastroduodenal diseases, the EAELQ variant rates in the gastric cancer and precancerous lesions groups were 86.67% and 70%, respectively, whereas those in the non-atrophic gastritis and peptic ulcers groups were only 47.37% and 44.44%, respectively. The difference in these rates was statistically significant (p=0.038). Conclusion: This preliminary study highlighted the genetic diversity of the H. pylori cagL gene, revealing distinct polymorphism patterns unique to Vietnam. The EAELQ variant at CagL residues 140–144 may serve as an indicator of gastric cancer risk.